PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH, KONDISI SOSIAL EKONOMI ORANG TUA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Laila Juma'diah Umi Safitri; Lilik Kustiani; Walipah Walipah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
This study aims to identify and analyze the effect of the use of the use of the school library, social-economic condition of parents and learning motivation towards learning outcomes integred IPS 8th grade student of SMPN 2 Pakisaji. This type of research is explanatory research using a quantitative approach. As for the data collection tehniques using questionnaires and documentation with total population of 109 and a sample of 53 student. Proportional sampling random sampling with random sampling techniques. The methode used is multiple linear regression. Based on test result obtained result that there is influence simultanneously between the use of the school library, socio-economic contion of parents, and learning motivation towards learning outcomes with significant values of 0,037 and partially on effect between the use of the school library to the learning outcomes with significant value 0,267, there is influence of socio-economic condition of parents on learning outcomes with significant value 0,088 and influence learning motivation towards learning outcomes with significant value 0,056.